INTERLINGUAL TRANSLATION: AN ATTEMPT AT UNDERSTANDING SOME BASIC CONCEPTS - Van, Hoang Van (VNU Journal of Foreign Studies; Vol 38 No 6DO - 10.25073/2525-2445/vnufs.4880, 2022)
This paper attempts to look at some small fragments of interlingual translation studies. The article begins by exploring Roman Jakobson’s tripartite division of translation of which interlingual translation is a component part. Then it presents in some detail the interlingual translation process. This is followed by two main sections where the core concept in interlingual translation theory and practice – “translation equivalence” (TE), some other concepts related to it, and three main approaches to TE are examined. It is clear from the paper that interlingual translation is a very complex social semiotic process, and that the concept of TE is employed in so many different senses that recently it has been denied by some scholars any value, or even any legitimate status in translation theory and translation practice. However, based on what is going on in the field of interlingual translation studies, it is suggested that the complexity of the interlingual translation process and the diversity of opinions on the concept of TE do not mean that scholars have complicated the problems. Rather, they have really contributed to the advancement of knowledge in the field, not with the intention of a final verdict, but as food for thought and invaluable reference materials for further research, making interlingual translation theory and practice an ever-moving academic discipline.